Maintenance management of kariah masjid: A preliminary study on the technical background of masjid’s maintenance staff in Federal Territory Kuala Lumpur - Ibrahim, Md. Najib; Abdul Rasid, Anis Azura; Yahya, Mohamad Ridzuan (2009)
Although maintenance works are normally outsourced, the officer in charge of maintenance of a masjid should have a basic technical background in building maintenance management. This is essential so that the maintenance problems are correctly identified for communication with top management as well as for follow-up maintenance work by appointed contractors. This paper presents the preliminary finding of a study on the technical background of masjid official responsible in building maintenance of selected masjids kariah in Federal Territory Kuala Lumpur, Malaysia. The finding may be used in drafting a suitable training module for them.